2016
DOI: 10.1073/pnas.1612734113
|View full text |Cite
|
Sign up to set email alerts
|

Fusion transcriptome profiling provides insights into alveolar rhabdomyosarcoma

Abstract: Gene fusions and fusion products were thought to be unique features of neoplasia. However, more and more studies have identified fusion RNAs in normal physiology. Through RNA sequencing of 27 human noncancer tissues, a large number of fusion RNAs were found. By analyzing fusion transcriptome, we observed close clusterings between samples of same or similar tissues, supporting the feasibility of using fusion RNA profiling to reveal connections between biological samples. To put the concept into use, we selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…The fusion transcriptome clustering with a binary input (present or absence of a chimera) behaved as well as traditional transcriptome clustering in human body maps 3 and uncovered a connection between normal myogenesis and ARMS 3 that could not be revealed by whole transcriptome analyses. Three factors may contribute to these results: (1) Gene expression profiles are highly influenced by changes in genes that are not associated with specific cell types; (2) In contrast, chimeric RNAs in general are often tightly associated with specific cancer types, and/or tissue differentiation lineages (manuscript in preparation); (3) Unlike the expression of most cellular genes, where the level of expression is used as a quantitative trait, the chimeric RNAs may be viewed as potential qualitative traits.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The fusion transcriptome clustering with a binary input (present or absence of a chimera) behaved as well as traditional transcriptome clustering in human body maps 3 and uncovered a connection between normal myogenesis and ARMS 3 that could not be revealed by whole transcriptome analyses. Three factors may contribute to these results: (1) Gene expression profiles are highly influenced by changes in genes that are not associated with specific cell types; (2) In contrast, chimeric RNAs in general are often tightly associated with specific cancer types, and/or tissue differentiation lineages (manuscript in preparation); (3) Unlike the expression of most cellular genes, where the level of expression is used as a quantitative trait, the chimeric RNAs may be viewed as potential qualitative traits.…”
mentioning
confidence: 67%
“…2 Recently, we demonstrated that fusion RNA profiling is a novel way to group biological samples and can reveal connections between samples. 3 Contradictory to the prevailing view that fusion RNAs are cancer-unique phenomena, we and others have showed that they are widespread in non-cancer cells and tissues. [4][5][6] We coined the phrase "fusion transcriptome," and demonstrated that "fusion RNA profiling" can cluster biological samples into separate groups of different tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PAX3–FOXO1 transcripts appeared to be limited to particular time points in the differentiation pathway, suggesting a role at certain stages of myogenic differentiation. Cells at these time points shared gene expression patterns with a fusion‐positive ARMS cell line . This suggests a non‐oncogenic role of the fusion protein and underlines the importance of cellular context and cooperating events.…”
mentioning
confidence: 67%
“…The following primers were used: TFF3 mRNA forward: 5′- TGAACTGACCTCTCCCCTTT -3′, reverse: 5′- CTGCTCTGGATTGTTTGCTTG -3′, VEGF mRNA forward: 5’- GCTACTGCCATCCAATCGAGAC-3’, reverse: 5’- CTATGTGCTGGCCTTGGTGA G-3’, CA9 mRNA forward: 5’- ACCTGGTGACTC TCGGCTACAG-3’, reverse: 5’- CAG CCAGGCAGGAA TTCAGC-3’, MMP2 mRNA forward: 5’- CCCACACTGGGCCCTGTCACT-3’, reverse: 5’- TGGGCTTGTCACGTGGCGTC-3’, GAPDH mRNA forward: 5′- CGGAGTC AACGGATTTGGTCGTAT -3′, reverse: 5′-AGCCTTCTCCATGGTGGTGAAGAC -3′ (TaKaRa). The comparative Ct (2 -ΔΔCt ) method was used [ 41 ].…”
Section: Methodsmentioning
confidence: 99%